Consumer Dispute Resolution Decision Policies and Business Implications - Rina Arum Prastyanti; Prattana Srisuk (Lembaga Contrarius Indonesia, 2026)
Consumer disputes between business actors and consumers continue to challenge the effectiveness of Indonesia’s consumer protection framework, particularly in the implementation of arbitration mechanisms. Law Number 8 of 1999 concerning Consumer Protection formally mandates the Consumer Dispute Resolution Agency to adjudicate disputes, yet regulatory and institutional limitations hinder the optimal execution of arbitration-based decisions. This study examines and analyzes the regulatory framework governing the execution of arbitration in consumer dispute resolution, identifies its normative and structural weaknesses, and formulates a justice-oriented reconstruction of the relevant provisions. The research applies a constructivist paradigm and adopts a sociological juridical approach. It integrates normative legal analysis with empirical field data to assess how arbitration functions in practice. The study systematically organizes and qualitatively analyzes both primary and secondary data to produce a comprehensive evaluation of the existing regulatory model. The findings demonstrate substantive inconsistencies between consumer arbitration procedures and the broader arbitration regime, structural weaknesses within the institutional framework of dispute resolution bodies, and limited consumer awareness regarding legal rights. These deficiencies reduce legal certainty and weaken the effectiveness of arbitration outcomes. The study concludes that lawmakers must reconstruct specific statutory provisions, particularly those governing the execution of arbitral decisions, in order to strengthen institutional coherence, enhance legal certainty, and ensure justice in consumer dispute resolution.